Validation of UV-Vis spectrophotometry methode for analysis of apigenin in celery extract (Apium graveolens L.) - Asep Nurrahman Yulianto; Taofik Rusdiana; Muchtaridi Muchtaridi; Anas Subarnas (Pharmaciana, 2017)
Apigenin is one of the flavonoid compounds contained in celery (Apium graveolens L.) and has been used for the treatment of various diseases. This study aims were to ensure the validity and accuracy of analytical method for apigenin assay in celery extract using UV-Vis spectrophotometry. The flavonoids test of celery extract give a positive result which produces a yellow color that can be drawn by amyl alcohol. The result of TLC test using a mobile phase of chloroform and methanol (9.5 : 0.5) produced Rf value of 0.75. Validation of analytical methods were sensitivity, linearity, limit of detection as well as limit of quantification, accuracy, and precision. Validation of analytical methods showed that sensitivity results as represented by molar extinction (Îµ) was 77004.35 M-1cm-1. Linearity from calibration curve at concentration of 2, 4, 6, 8, and 10 mgL-1 resulted an equation of y = 0.074x â€“ 0.0011 with coefficient correlation (r) of 0.9996. The limit of detection and limit of quantification were 2.99 mgL-1 and 9.92 mgL-1 respectively with recovery percentage of 97.59% and the coefficient variation values were 1.53%; 2.43% and 1.68%. The average contents of apigenin in the celery extract were of 3.74 Â± 0.09%.Â